A Primer for Benefit–Cost Analysis - Richard O. Zerbe Jr., Allen S. Bellas (Edward Elgar Publishing, 2006)
The purpose of this book is to provide clear and relatively straightforward guidelines for conducting proper benefit–cost analyses (BCAs) of proposed or previously enacted public projects. Alternatively, the purpose of this book is to allow the reader to critically examine BCAs encountered in the course of work or study. While it might be nice to believe that all analyses are correctly and responsibly done, existing studies demonstrate a great range of levels of quality. The concepts and techniques presented here are not an exhaustive discussion of BCA, but rather are a summary of the most important features of an analysis. The techniques outlined here will generate correct analyses. Most of the presentation should be accessible to anyone with a good understanding of economics, although some topics use indifference curve analysis or some basic calculus. The great advantage of BCA is that it provides an objective framework around which discussion, correction and amendment can take place. Its greatest risk is that hard numbers will tend to drive out soft. Care must be taken that unquantified or roughly quantified effects be given their proper weight. In doing this it is useful as well as politically realistic to regard BCA as an aid to discussion and to decision and not as the decision itself. BCA should not be a mysterious process. Stated quite simply, it is the calculation of values for all the inputs into and outputs from a project and then the subtraction of the first from the second. At times some intricate procedures might be used to determine the value of a good for which a price is not readily available, but the core concepts of BCA are fairly simple.